Inovasi Pangan Lokal: Pelatihan Pembuatan Perkedel Singkong sebagai Alternatif Makanan Bernilai Gizi di Desa Pulau Panjang, Kecamatan Pulau Ampel, Kabupaten Serang, Provinsi Banten - Adinda Syafira; Ibnu Damar Nuruddin; Wulan Putri Amellia; Tania Syahputri; Reza Abdillah; Sindi Indriyawati; Nurralim Nurralim; Ariestawidya Kinasih Azzahra; Fajri Drajat Pradika; Syahmaniar Fariski; Muhammad Rafli Muttaqim; Bella Rosadi (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Food security and nutrition remain important issues in coastal areas with limited access to diverse food sources. This community service program was conducted in Pulau Panjang Village, Pulau Ampel Subdistrict, Serang Regency, Banten Province, with the aim of empowering the local community through cassava based food innovation a nutritious and locally available commodity. The objective of the program was to introduce cassava fritters (perkedel singkong) as an alternative nutritious food and to enhance community knowledge and skills in cassava processing. The methods involved initial surveys (pre-tests), educational sessions, hands-on food processing activities, and final surveys (post-tests) to evaluate the effectiveness of the intervention. The training was designed using a participatory approach, allowing community members to be actively involved in each stage of the program. The results indicated an improvement in participants’ understanding of cassava’s nutritional value and its potential for home consumption and microenterprise development. Most participants showed interest in adopting cassava fritters as part of their daily meals and even as a potential small business product. This program effectively increased nutritional awareness, supported local food diversification, and strengthened community based food resilience through participatory education and innovation.